The Effectiveness of Meritocracy in Structural Position Promotion at the Central Statistics Agency of East Nusa Tenggara Region (Study at the Central Statistics Agency in Mainland Timor) - KASE, Yudith; NEOLAKA, Melkisedek N.B.C.; DJAHA, Ajis Adang (Journal of Tourism Economics and Policy, 2025)
One of the efforts to strengthen institutional governance and drive bureaucratic reform at the Central Statistics Agency (BPS) is the implementation of a meritocracy system. This system aims to build competitive and professional human resources within the framework of good governance. In the bureaucratic reform agenda, meritocracy is crucial for promoting fairness and competence while minimizing nepotism, corruption, and transactional practices in job promotions. This study examines the effectiveness of the meritocracy system in promoting structural positions within BPS East Nusa Tenggara, focusing on echelon III and IV roles. It also explores supporting and inhibiting factors in its implementation. A descriptive qualitative approach was employed, using observation, document review, and interviews for data collection. Data analysis included reduction, presentation, and conclusion drawing. Duncan's theory—goal achievement, integration, and adaptation—was used to assess effectiveness, while Grundmann’s merit principles—recruitment, selection, equity, retention, neutrality, and public interest—were applied to identify influencing factors. Findings indicate that the meritocracy system in BPS East Nusa Tenggara is still relatively ineffective. Key inhibiting factors include the absence of formal regulations at the echelon II level, inadequate assessment of non-technical qualifications, lack of interest in echelon IV roles, and limited budget to support merit-based practices. Suggested improvements include broader use of assessment centers, proposing additional budgets for external selection processes, and revising job profiles and allowances to enhance role attractiveness and employee welfare.